Housing in Brussels: diagnosis and challenges - Christian Dessouroux; Rachida Bensliman; Nicolas Bernard; Sarah De Laet; François Demonty; Pierre Marissal; Johan Surkyn (Brussels Studies)
This synopsis highlights the various facets of the housing problem in Brussels through different approaches (demographic, legal, political and sociological). It does not constitute an exhaustive state of knowledge regarding housing, but presents a panorama of current knowledge and challenges. It highlights the different dimensions of housing in the context of demographic growth and social fragmentation, reveals the controversies and debates on this subject and points out the main challenges for the future.